Three-sided football: DIY football and social transformationalism. Issue 9 (22nd November 2021) - Pollock, Benjin
ABSTRACT : Devised as an illustrative example of 'triolectics', Danish artist and philosopher Asger Jorn first conceived of three-sided football (3SF) in 1962 as a way to radically transform the world. However, 3SF remained a purely abstracted philosophical concept until 1994 when a group of anarchists, architects and artists decided to play the game for the first time. Since these early experiments, 3SF has been played and developed across the globe, from anti-racist football festivals in Germany, contemporary art installations in France, through to youth outreach programs in Colombia. Far beyond its emergent context, the game continues to resonate for a myriad of social actors in search of bottom-up ways to enact transformational change in contemporary culture. Drawing from forty-four semi-structured interviews with players, coaches, curators and activists, this paper provides the first ethnography into 3SF and privileges much needed perspectives into how 'DIY Football' initiatives are actively redefining individual and collective relationships to sport and politics in informal volunteer settings. Utilising the work of Bourdieu as a useful conceptual heuristic, it details how participants reflect upon, and negotiate, the challenges of reaching beyond the 'doxic logics' of binary competitive team sport. Moreover, how the democratic 'desportised' spaces of 3SF transcend quotidian sporting contexts and offer distinct forms of political renewal, social inclusion and practical education. This study further contends that the horizontalist non-hierarchical nature of the game develops critical consciousness and community leadership for those involved in the play.